2012
DOI: 10.1155/2012/712617
|View full text |Cite
|
Sign up to set email alerts
|

The Common C49620T Polymorphism in the Sulfonylurea Receptor Gene SUR1 (ABCC8) in Patients with Gestational Diabetes and Subsequent Glucose Metabolism Abnormalities

Abstract: Aim. The aim of this study is to investigate the relationship between the common C49620T polymorphism in the sulfonylurea receptor (SUR1) gene and glucose metabolism, β-cell secretory function and insulin resistance in women with a history of gestational diabetes (GDM). Material and Methods. Study group included 199 women, diagnosed GDM within the last 5–12 years and control group of comparable 50 women in whom GDM was excluded during pregnancy. Blood glucose and insulin levels were measured during oral glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Our study showed predominance of the T allele over the C allele with a significant risk ( p < 0.05) of T2D. This is in contrast to findings from other regions across the globe where the wild type C allele is usually predominant in the population [ 23 , 24 ]. The homozygote mutant TT genotype was more frequent than the homozygote wild type CC genotype while the heterozygote CT was the least frequent.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed predominance of the T allele over the C allele with a significant risk ( p < 0.05) of T2D. This is in contrast to findings from other regions across the globe where the wild type C allele is usually predominant in the population [ 23 , 24 ]. The homozygote mutant TT genotype was more frequent than the homozygote wild type CC genotype while the heterozygote CT was the least frequent.…”
Section: Discussioncontrasting
confidence: 99%
“…Number of human genes was investigated dealing with GDM: HLA, SUR1 (sufonylurea receptor gene), GCK (glucokinase gene), TCF7L2 (transcription factor 7-like 2 gene), HFE (hemochromatosis gene) and others with contradicting results [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%